Upaya Meningkatkan Hasil Belajar IPA Dengan Model Probex (Predict, Observe, Explian) - Nurlisma Nurlisma (JURNAL GLOBAL EDUKASI, 2018)
Abstract: In general, the value of science learning outcomes achieved by students of SMP Negeri 12 Pekanbaru on the Material Pressure concept is still low. Many students feel bored and lack enthusiasm in learning. This is because the teacher is too monotonous and lacks a variety of methods in learning. The purpose of this study was to improve the Learning Outcomes of Science in the subject matter of Pressure on students of class VIII.8 of SMP Negeri 12 Pekanbaru through the application of the Probex model. This research is a classroom action research, which consists of 2 cycles, where each cycle consists of planning, implementation, observation and reflection. The results showed that the application of the Probex model could improve science learning outcomes in the subject matter of Pressure on VIII.8 grade students of 12 SMP Negeri Pekanbaru 2016/2017 Academic Year, ie before the completion of completeness was only 39%, after the first cycle reached 60.97% and after the implementation of the second cycle reached 79.05%. Keywords: probex, predict, observe, explain Abstrak: Pada umumnya nilai hasil belajar IPA yang dicapai siswa SMP Negeri 12 Pekanbaru pada materi Konsep Tekanan masih rendah. Banyak siswa yang merasa bosan dan kurang bersemangat dalam belajar. Hal ini disebabkan kerena guru terlalu monoton dan kurang memberikan variasi metode dalam pembelajarannya. Tujuan penelitian ini adalah untuk meningkatkan Hasil Belajar IPA pada materi pokok Tekanan pada siswa kelas VIII.8 SMP Negeri 12 Pekanbaru melalui penerapan model Probex. Penelitian ini merupakan penelitian tindakan kelas, yang terdiri 2 siklus, dimana masing-masing siklus terdiri dari perencanaan, pelaksanaan, observasi dan refleksi. Hasil penelitian menunjukkan bahwa penerapan model Probex dapat meningkatkan hasil belajar IPA pada materi pokok Tekanan pada siswa kelas VIII.8 SMP Negeri 12 Pekanbaru Tahun Pelajaran 2016/2017, yaitu sebelum perbaikan ketuntasan hanya 39%, setelah siklus I mencapai 60,97% dan setelah pelaksanaan siklus II mencapai 79,05%. Kata kunci: probex, predict, observe, explain